2006
DOI: 10.1021/np058128n
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products from Plant-Associated Microorganisms:  Distribution, Structural Diversity, Bioactivity, and Implications of Their Occurrence

Abstract: A growing body of evidence suggests that plant-associated microorganisms, especially endophytic and rhizosphere bacteria and fungi, represent a huge and largely untapped resource of natural products with chemical structures that have been optimized by evolution for biological and ecological relevance. A diverse array of bioactive small molecule natural products has been encountered in these microorganisms. The structures of over 230 metabolites isolated and characterized from over 70 plant-associated microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
522
1
56

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 954 publications
(584 citation statements)
references
References 130 publications
5
522
1
56
Order By: Relevance
“…11,12,14 It is widely believed that the potential of secondary metabolites with biological activities from endophytic actinomycetes is just as great as that achieved from soil actinomycetes. [16][17][18][19][20] As results of our exploration, we have already found several novel compounds from endophytic actinomycetes. In a similar vein, many new genera of actinomycetes, such as Allonocardiopsis from the fruit of a medical plant, 21 Actinophytocola from Thai glutinous roots of rice plants, 22 Plantactinospora from root of a medical plant, 23 had been discovered and promising endophytes with unknown function may arise from plants.…”
Section: Introductionmentioning
confidence: 92%
“…11,12,14 It is widely believed that the potential of secondary metabolites with biological activities from endophytic actinomycetes is just as great as that achieved from soil actinomycetes. [16][17][18][19][20] As results of our exploration, we have already found several novel compounds from endophytic actinomycetes. In a similar vein, many new genera of actinomycetes, such as Allonocardiopsis from the fruit of a medical plant, 21 Actinophytocola from Thai glutinous roots of rice plants, 22 Plantactinospora from root of a medical plant, 23 had been discovered and promising endophytes with unknown function may arise from plants.…”
Section: Introductionmentioning
confidence: 92%
“…It is generally recognized that endophytes represent an important and largely untapped reservoir of unique chemical structures that have been modified through evolution (Gunatilaka 2006;Kharwar et al 2011) and exhibit the capability to produce the same functional compounds as their hosts, some examples include taxol (Stierle et al 1993(Stierle et al , 1995, podophyllotoxin , hypericin (Kusari et al 2008), and azadirachtin (Findlay et al 1997). In 2005, Puri et al reported the first discovery of CPT-producing endophytic fungus Entrophospora infrequens from the inner bark of N. foetida, which set the stage for a more comprehensive examination of other plants for the presence of CPT-producing endophytes Rehman et al 2008Rehman et al , 2009Kusari et al 2009;Shweta et al 2010Shweta et al , 2013Gurudatt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi living within plant tissues have proven to be a promising source for the production of structurally novel and pharmacologically active secondary metabolites [1]. As a result of our ongoing efforts to identify new compounds from endophytes, new metabolites were reported from strains of Xylaria sp.…”
Section: Introductionmentioning
confidence: 99%